Determinan Penyerapan Tenaga Kerja di Provinsi Jawa Timur - Safitri, Anis Wahyu; Desmintari, Desmintari (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Labor absorption is one of the important factors that influence the development of a region's workforce. Labor is a big complex problem because it affects and is influenced by many factors such as the quality of human resources, high-quality output and high-value wages. This research was conducted with the aim of knowing the determination that affects the absorption of labor in the Regency/City in East Java Province. The data used is data from 29 regencies and 9 cities in East Java Province in the form of GRDP, HDI, Minimum Wage and Investment data in 2016-2020. In this study using panel data with the research model Fixed Effect Model. The results show that GRDP, HDI have a not significant positive effect on labor absorption in East Java and Wages have a significant positive effect on labor absorption in East Java. While the investment variable has a significant negative effect on labor absorption in East Java.